Many losers and a few winners: The impact of COVID‐19 on Canadian industries and regions. (1st December 2021) - Slade, Margaret E.
Abstract: COVID‐19 has affected all industrial sectors and regions of the world and, in many cases, the impact has been devastating. Nevertheless, there are large differences across sectors and regions, with a few winners as well as many losers. This paper assesses the impact of the first wave of the virus on Canadian industries and provinces in the short and medium run. In particular, time series forecasting models for 39 three‐digit industries in each of the 10 provinces are estimated and used to predict post‐lockdown losses: percentage differences between forecast and observed economic activity. Econometric analysis of the estimates is then used to quantify and rank industries and provinces in terms of short‐ and medium‐term losses and gains. Provincial ranks are then compared with the stringency of provincial economic restrictions. Résumé: De nombreux perdants et quelques gagnants : incidence de la COVID‐19 sur les industries et les régions canadiennes. La crise de la COVID‐19 n'a épargné aucun secteur industriel ni aucune région du monde, et dans la plupart des cas, les conséquences se sont avérées dévastatrices. Néanmoins, l'on observe de grandes disparités d'un secteur à l'autre et d'une région du monde à l'autre, avec quelques gagnants mais également de nombreux perdants. Cet article évalue l'incidence de la première vague du virus sur les industries et les provinces canadiennes à court et à moyen terme. De manière plus spécifique, et afin de prévoir les pertes consécutives au confinement, nous estimons et utilisons des modèles de prévision chronologique pour les 39 industries à trois chiffres dans chacune des dix provinces du pays. Nous calculons ainsi les écarts de pourcentage entre l'activité économique estimée et celle observée. Nous utilisons ensuite l'analyse économétrique de nos évaluations pour mesurer et classer les différentes industries et provinces en termes de gains et pertes à court et moyen terme. Les classements des provinces sont ensuite comparés à l'aune de la rigueur des restrictions économiques mises en place au niveau local.